Coeliac disease and autoimmune thyroid disease. Issue 6 (June 1994) - Counsell, C E; Taha, A; Ruddell, W S
Abstract : A well defined cohort of coeliac patients was studied prospectively to assess the prevalence of coexisting thyroid disease and positive thyroid autoantibodies. Comparison with epidemiological data on the prevalence of coeliac disease in a neighbouring area suggested that few adult coeliac patients had been missed. Overall, 14% of the coeliac patients had thyroid disease: 10.3% were hypothyroid and 3.7% hyperthyroid, both significantly more than expected. There were significantly more coeliac disease patients with thyroid autoantibodies than expected--11% had thyroglobulin antibodies and 15% had thyroid microsomal antibodies. This association is clinically important. Three patients are described in whom the coexistence of coeliac disease and hypothyroidism led to diagnostic difficulties and delay of treatment.